Colaboradores - Torres, Laura Christiane (Faculdade de Filosofia e Ciências, 2015)
Barnabé Malcalza Bruno Theodoro Luciano Cauê Rodrigues Pimentel  Chaldeans Mensah Frederico de Almeida Castro Marinho  Lara Martim Rodrigues Selis Raphael Camargo LimaRodrigo Duarte Fernandes dos Passos Sara Maria Costa Garay